Haematogenous Periprosthetic Hip Joint Infection Caused by Salmonella May Be Paucisymptomatic: A Report of 2 Cases - Lara Pozzi; Corina Dommann-Scherrer; Christoph Meier; Peter Wahl (Case Reports in Orthopedic Research, 2022)
Periprosthetic joint infection (PJI) with Salmonella is rare. We therefore describe two cases of PJI with Salmonella spp. Case one is a 79-year-old female that presented with fever and acute left hip pain 16 months after revision total hip arthroplasty (THA) performed due to instability. Case two is a 82-year-old male after revision THA due to periprosthetic pseudotumor 22 years after THA. Microbiological work up of intra-operatively obtained specimen showed growth of Salmonella spp. In both patients, implant-retaining treatment was successful. Patients with PJI with Salmonella may be oligosymptomatic, potentially delaying the diagnosis. Successful implant-retraining treatment is possible.